ANALISIS EFEKTIVITAS KIPAS-KIPAS SEBAGAI ALTERNATIF ALAT TANGKAP ANAKAN LOBSTER DI DESA RANOOHA RAYA - Fajriah Fajriah (Jurnal Bisnis Perikanan (Journal of Fishery Business), 2017)
One of the fishing gear used by fishermen in Ranooha Raya Village is a lobster tiller that they call "fans". Lobster tiller is a tool used to trap lobster pups directly from the sea to help with the availability of tillers to be raised. Until now there has been no research on this fishing gear even though it has produced quite a lot of lobster chicks. So it is very important to do research with the aim of knowing the effectiveness of using "fan" fishing tools as an alternative to lobster tiller, design and construction of fans and their use. Furthermore, for the level of effectiveness analyzed by analysis of effectiveness and to find out the existence of fishing gear whether it is feasible to be developed analyzed using SWOT. Use survey and interview methods and test the manufacture of fishing gear fans. The results of the study showed a low level of effectiveness at each station/fishing gear installation position at the time the research was conducted. Recommendations for use that are produced include: Regulating the area and time of arrest, forming a group of fishermen and Pokmaswas, supporting academics, assisting the fishing fleet by the government and involving the community in making regulationsOne of the fishing gear used by fishermen in Ranooha Raya Village is a lobster tiller that they call "fans". Lobster tiller is a tool used to trap lobster pups directly from the sea to help with the availability of tillers to be raised. Until now there has been no research on this fishing gear even though it has produced quite a lot of lobster chicks. So it is very important to do research with the aim of knowing the effectiveness of using "fan" fishing tools as an alternative to lobster tiller, design and construction of fans and their use. Furthermore, for the level of effectiveness analyzed by analysis of effectiveness and to find out the existence of fishing gear whether it is feasible to be developed analyzed using SWOT. Use survey and interview methods and test the manufacture of fishing gear fans. The results of the study showed a low level of effectiveness at each station/fishing gear installation position at the time the research was conducted. Recommendations for use that are produced include: Regulating the area and time of arrest, forming a group of fishermen and Pokmaswas, supporting academics, assisting the fishing fleet by the government and involving the community in making regulations.